Nicotine Inhibits Clostridium difficile Toxin A-Induced Colitis but Not Ileitis in Rats. (11th January 2016) - Vigna, Steven R.
Abstract : Nicotine is protective in ulcerative colitis but not Crohn's disease of the small intestine, but little is known about the effects of nicotine on Clostridium difficile toxin A-induced enteritis. Isolated ileal or colonic segments in anesthetized rats were pretreated with nicotine bitartrate or other pharmacological agents before intraluminal injection of toxin A. After 3 hours, the treated segments were removed and inflammation was assessed. Nicotine biphasically inhibited toxin A colitis but not ileitis. Pretreatment with the nicotinic receptor antagonist, hexamethonium, blocked the effects of nicotine. Pretreating the colonic segments with hexamethonium before toxin A administration resulted in more inflammation than seen with toxin A alone, suggesting that a tonic nicotinic anti-inflammatory condition exists in the colon. Nicotine also inhibited toxin A-induced increased colonic concentrations of the TRPV1 (transient receptor potential vanilloid subtype 1) agonist, leukotriene B4 (LTB4 ), and release of the proinflammatory neuropeptide, substance P. Pretreatment with nicotine did not protect against direct TRPV1-mediated colitis caused by intraluminal capsaicin. Nicotinic cholinergic receptors tonically protect the colon against inflammation and nicotine inhibits toxin A colitis but not toxin A ileitis in rats in part by inhibition of toxin A-induced activation of TRPV1 by endogenous TRPV1 agonists such as LTB4 .